Designing for print production essential concepts - Luttropp, John C. (Delmar/Cengage Learning, 2009)
Combining print design concepts with graphic production technology information, this work provides readers with an understanding of the processes involved in the design and print/publishing fields. It focuses on the content, concepts and instructional strategies that are relevant, and is suitable for those in the design and production fields.